Developing a Profile to Improve Competitiveness in Debating of Undergraduates with Mathematical Logic - Thevaka, S.; Aqeela, M.R.F. (Faculty of Humanities and Social Sciences, University of Sri Jayewardenepura, Sri Lanka, 2021)
Competing lies in the heart of every debate and it can be existing for the students who follow the degree programme in specialization of Human Resource Management. In recent years one trend has been to argue that it is necessary to intervene ‘strategically’ in such debates competition. Educators are seeking to develop thinking skills would likely consider their efforts largely successful if students became proficient in advancing, critiquing, and defending claims in reasoned discussion with peers. The proof of a good debate lies in the skills of the debaters to convey their message to present their arguments convincingly and to rebut the arguments of their opponents in a logical and persuasive way. Oral mathematical and logical communication can be used as a tool to communicate effectively in such debating process. Our work is motivated the management undergraduate students by providing strategies to compete debate competition and arguments with proper justification with the connection of mathematical logic reasoning concepts. This research is a qualitative study. Participants selected from final year students of BBM Honours in Human Resource Management undergraduates of Vavuniya Campus who are involving in debate competitions. Data was collected through in-depth interview. The transcribed data was translated into mathematical language based on the theoretical framework of oral mathematical communication. Finally, the study derived an algorithm for the demonstration of debate competition by mathematical logic reasoning.
Keywords: Argument; Debate; Mathematical Logic; Oral Mathematical Communication; Debating Strategies